БИЛИМЛЕНДИРИЎ СЫПАТЫН АСЫРЫЎДА ПЕДАГОГИКАЛЫҚ ТЕХНОЛОГИЯЛАРДАН ПАЙДАЛАНЫЎДЫҢ ӘҲМИЙЕТИ - ДЖамилова, Г.Ж. (FAN va JAMIYAT, 2020)
The article deals with importance of using pedagogical technologies in enhaciug quality of education burtuemore it presents the difference of pedagogical collaboration with traditional one.